Effect of Activation Time on the Pinang Frond Based Activated Carbon for Remazol Brilliant Blue R Removal - Ahmad, Mohd Azhar; Herawan, Safarudin Gazali; Yusof, Ahmad Anas (2013)
Activated carbons are regularly used for dyes wastewater treatment. It can be produced from various organics materials which having high level of carbon content. In this study, pinang frond based activated carbon (PFAC) was produce by using physical activation process to study the effect of difference activation time in the range of 1-7 hours. The optimum PFAC sample is found on activation time of 3 hours which gives the highest BET surface area and pore volume of 958.23 m2/g and 0.5469 mL/g, respectively. This sample shows well-developed pore structure with high fixed carbon content of 79.74%. The removal of remazol brilliant blue R (RBBR) by 87.6 % for initial RBBR concentration of 50 mg/L and 40.8 % for 500 mg/L are achieved via this sample.